Cognitive Ability and Paternalism - Gilles Saint-Paul (Institute for the Study of Labor (IZA), 2002)
This paper analyses the welfare effects of price restrictions on private contracting in a world where agents have a limited cognitive ability. People compute the costs and benefits of entering a transaction with an error. The government knows the distribution of true costs and benefits as well as that of errors. By imposing constraints on transaction prices, the government eliminates some that are on average inefficient–because the price signals that one of the parties has typically grossly overestimated its benefit from participation. This policy may increase aggregate welfare even though some of the transactions being blocked are actually efficient. The paper also studies the extent to which the use of private consultants with sufficient intelligence by people with limited intelligence may dominate government regulation.
Keywords: K32; K31; J8; J42; J41; J38; I3; H21; D83; D82; D81; 330; cognitive ability; minimum wages; regulation; price controls; paternalism; intelligence; Preisaufsicht; Rationales Verhalten; Beschränkte Rationalität; Kognition; Theorie